Project Surveyor Lunar Gas Chromatograph (1962)
A set of color and black and white photographs depict the gas chromatograph from various angles. In two photographs, a package of Marlboro cigarettes sits beside the instrument, presumably to provide a sense of scale. The lunar gas chromatograph was developed, under a JPL contract, to analyze lunar soil. Payload reductions meant that this instrument did not fly on the lunar lander, but it met the performance and environmental requirements of Project Surveyor.
Keywords: United States. National Aeronautics and Space Administration; Scientific apparatus and instruments; Surveyor Program (U.S.); Gas chromatography; Gas chromatography--Instruments; Jet Propulsion Laboratory (U.S.); Cigarettes; Beckman Instruments, Inc.